Soil microbial consortium and enzymatic activity with conservative N doses on legume-maize cropping sequence - Sai Kishore, A; Sreelatha , D; Malla Reddy, M; Nagesh, K M V; Sukruth, K T (Plant Science Today, 2025)
The save soil campaign and the recent international summit, COP-28, highlighted the importance of soil microbial fauna in the ecosystem for the years to come, which supports soil-plant symbiosis under current dire conditions. The inclusive recycling of garbage into feasible residues is necessary to boost nitrogen (N) levels in order to combat climate change and encourage responsible production in accordance with Sustainable Development goals (SDG) . Using these residues to boost the activity of the microbial community that is present both above and below the rhizosphere including endospheric diazotrophs in the legume-maize system is a significant benefit. This study examined a legume (Groundnut, Soybean, Greengram)-Maize sequence with varying nitrogen rates (100 %, 125 %, 150 % N) in a split-plot design using different treatment combinations during the kharif and rabi seasons of successive periods. The results indicated that the sustained biomass of greengram for rabi maize under zero-till conditions led to a progressive improvement in bacterial consortium activity up to 60 days and enzymatic activity from one cropping cycle to the next, compared to soybean and groundnut. Furthermore, a 50 % deviation from normal nitrogen rates proved superior to 25 % and 0 % nitrogen, revealing the importance of the C:N ratio of biomass and the decomposition process in accelerating consortium activity for improved fertility. Additionally, a rotating pulse crop serves as a vital component for rhizospheric nodulation and the soil microbial community, as the continuous cultivation of greengram demonstrates elevated soil consortium activity at higher levels. Moreover, the interaction (Legume biomass X Nitrogen rates) on zero-till maize was found to be minimal.